Post feline infectious peritonitis progressive hydrocephalus: a case series - Clouse, Mallory; Detwiler, W. Ryan; Gibson, Erika A.; Eich, Jessica; Berg, Jason; Joseph, Richard (Frontiers in Veterinary Science, 2025)
BackgroundWhile in recent years, great strides have been made in treating cats with feline infectious peritonitis (FIP), long-term sequelae of the disease are unknown.ObjectivesWe aimed to describe the MRI findings of cats who were presented for follow-up care post-treatment with GS-441524.AnimalsFour cats who underwent treatment for FIP diagnosed based on MRI and were re-presented 13–15 months post-treatment were evaluated. Three cats were re-presented with vestibular signs.MethodsCases were selected based on clinical signs and history of treatment of neurologic FIP. All cats were examined by a veterinary neurologist or neurology resident at each appointment. All MRIs were reviewed by a board-certified veterinary radiologist. Necropsy of Cat 2 was performed by a board-certified veterinary pathologist. Details of diagnostic test results and treatment were retrospectively acquired by review of medical records. Cerebrospinal fluid (CSF) analysis was performed and interpreted by a board-certified veterinary pathologist at an outside reference laboratory. FCoV PCR testing was submitted to university reference and commercial reference laboratories.ResultsAll cats presented had been treated with owner-sourced GS-441524 (off-label) for the standard 84 days. All cats improved clinically after treatment, evidenced by neurologic exam findings and owner reports. Three affected cats were re-presented for neurologic decline >1 year post-treatment; one cat remained neurologically stable. After MRI confirmed progressive hydrocephalus in the three affected cats, all were treated with ventriculoperitoneal (VP) shunt placement, with noted improvement in neurologic status post-operatively. The fourth cat showed improvement of hydrocephalus on MRI based on ventricular size. CSF analysis was performed for all cats, showing no evidence of active inflammation. CSF of three cats were negative for FCoV PCR (one cat had insufficient quantity collected for testing). One affected cat was euthanized for recurrent urinary obstruction; necropsy showed moderate to severe hydrocephalus with mild parenchymal collapse, and no evidence of active infection or inflammation was noted.Conclusion and clinical importanceProgressive post-FIP hydrocephalus should be a differential for cats re-presenting with neurologic signs after treatment for FIP with GS-441524. As the treatment is now legally available in the United States, more cases are likely to occur. It is important to differentiate these progressive post FIP hydrocephalus cases from relapses of FIP, as prognosis and treatment differ.